Весёлые стихи: [для младшего школьного возраста] / С. Михалков; художники: В. Сутеев и др. - Михалков Сергей Владимирович (Книжка за книжкой, 2018)
Экземпляры: ф.18 (20181008) / Инвентарный номер: 3001 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: М 69 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5